THE EFFECT OF FRAUD ON PROFITABILITY OF LISTED DEPOSIT MONEY BANKS IN NIGERIA (Malaysian Management Journal, 2021)
The increasing rate of fraud occurrence and poor profitability rate in the listed Deposit Money Banks (DMBs) in Nigeria calls for a research investigation. To unravel the likely connection between fraud and profitability, this study has examined the effect of fraud on the profitability of listed DMBs in Nigeria. To achieve this objective, the study adopted a correlational research design and utilised secondary data extracted from the Nigerian Deposit Insurance Commission (NDIC) and published financial statements of the DMBs. The study focused on 14 listed DMBs for a six-year period (2012-2017). Panel multiple regression technique was used to estimate the model of the study. The findings showed that fraud (proxied by actual loss from fraud and staff involvement in fraud) has a negative and significant effect on profitability (proxied by return on asset) of listed DMBs in Nigeria. In line with the findings, this study has recommended that listed DMBs should establish fraud detection mechanisms which will entail the setting up of an efficient, reliable and functioning fraud detection unit to monitor transactions that may be susceptible to fraud.